2019
DOI: 10.1136/gutjnl-2019-318760
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of genome-wide association studies and functional assays decipher susceptibility genes for gastric cancer in Chinese populations

Abstract: ObjectiveAlthough a subset of genetic loci have been associated with gastric cancer (GC) risk, the underlying mechanisms are largely unknown. We aimed to identify new susceptibility genes and elucidate their mechanisms in GC development.DesignWe conducted a meta-analysis of four genome-wide association studies (GWASs) encompassing 3771 cases and 5426 controls. After targeted sequencing and functional annotation, we performed in vitro and in vivo experiments to confirm the functions of genetic variants and cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…[3] Infection with the bacterium causes chronic gastritis. [4] In a minority of susceptible individuals, [5] this can lead to a stepwise progression through gastric atrophy, intestinal metaplasia, and dysplasia, to the development of carcinoma. [6] As a result, H.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Infection with the bacterium causes chronic gastritis. [4] In a minority of susceptible individuals, [5] this can lead to a stepwise progression through gastric atrophy, intestinal metaplasia, and dysplasia, to the development of carcinoma. [6] As a result, H.…”
Section: Introductionmentioning
confidence: 99%
“…For gastric cancer (case:control=1:191), both TAPE and TAPE-LTFH identified 3 genome-wide significant clumped variants (rs760077, rs35972942, rs2978977) while no variants were genome-wide significant by SAIGE. The three clumped variants have been previously reported to be associated with gastric cancer among Chinese or Japanese population [22][23][24] , but not among Korean samples. Manhattan plots and Q-Q plots are presented in Supplementary Figures 10 and 11.…”
Section: Analysis Of Binary Traits In Biobank Datamentioning
confidence: 87%
“…To rationalize the vital role of PUS7 in OV, we explored the proteins interacting with PUS7, which may partially help explain PUS7 function in tumor diagnosis, tumorigenesis, and development. The PPI and gene network analyses identified PUS7 interacting partners, including NOC3L and PUS1, which are also not reported in ovarian cancer, although several reports have revealed that NOC3L regulates the proliferation and tumorigenesis of gastric cancer [ 41 ], and NOC3L is associated with an increased risk of gastric cancer in the Chinese Han population [ 42 ]. For PUS1, previous reports demonstrated that it is related to sideroblastic anemia [ 43 ], and no association of PUS1 with cancer was ever shown, suggesting the novelty of the protein interaction.…”
Section: Discussionmentioning
confidence: 99%